Exogenous melatonin delays oxidative browning in litchi during cold storage by regulating biochemical attributes and gene expression - Kilchira A. Marak; Hidayatullah Mir; Mohammed Wasim Siddiqui; Preeti Singh; Fozia Homa; Saud Alamri (Frontiers in Plant Science, 2024)
Oxidative damage leading to loss of nutritional quality and pericarp discoloration of harvested litchi fruits drastically limits consumer acceptance and marketability. In the present investigation, the impact of postharvest melatonin application at different concentrations, i.e., 0.1 mM, 0.25 mM, and 0.5 mM, on fruit quality and shelf life of litchi fruits under cold storage conditions was studied. The results revealed the positive effect of melatonin application at all concentrations on fruit quality and shelf life. However, treatment with 0.5 mM concentration of melatonin resulted in minimum weight loss, decay loss, pericarp discoloration, and also retained higher levels of TSS, acidity, total sugar, ascorbic acid, anthocyanin, antioxidant, and phenolics content during cold storage. Melatonin administration also restricted the enzymatic activity of the polyphenol oxidase (PPO) and peroxidase (POD) enzymes in the fruit pericarp and maintained freshness of the fruits up to 30 days in cold storage. At the molecular level, a similar reduction in the expression of browning-associated genes, LcPPO, LcPOD, and Laccase, was detected in preserved litchi fruits treated with melatonin. Anthocyanin biosynthetic genes, LcUFGT and LcDFR, on the other hand showed enhanced expression in melatonin treated fruits compared to untreated fruits. Melatonin, owing to its antioxidant properties, when applied to harvested litchi fruits retained taste, nutritional quality and red color pericarp up till 30 days in cold storage.